Disfungsi Kebijakan CSR sebagai Instrumen Pemerataan Manfaat Tanah Perkebunan - Lailil Maghfiroh; Aldiska Aqsyal Pratama; Aqila Hafiya; Levy Nugraha Prayogo; Prameswari Bunga Kedaton (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
Corporate Social Responsibility, which in its implementation is often inversely proportional to what several companies should do, especially regarding the distribution of the benefits of plantation land to the surrounding community, will cause various types of losses. There are still no implementing regulations regarding Corporate Social Responsibility obligations in Indonesia, making this topic interesting for the author to study, with the hope that this research can help further research that will be carried out. The research method that the author uses is a normative juridical research method, using primary and secondary data sources. The authors' conclusion from this research is that some companies may not fully prioritize their Corporate Social Responsibility obligations, and the lack of clear sanctions may result in negligence. Therefore, it is necessary to improve regulations regarding administrative, civil, and criminal sanctions to ensure that the implementation of Corporate Social Responsibility is more structured, measurable, and has a greater positive impact.